An Analysis of the Effectiveness of Understudy Programs: The Case of the Roads Authority Namibia - KASIKA, Chalwa Gladys; DANGAREMBIZI, Fanuel (Management Dynamics in the Knowledge Economy, 2019)
There is a lack of effective, comprehensive understudy training programs in the Roads Authority (RA) of Namibia, compounded by a lack of monitoring and evaluation mechanisms of such programs. Minimal research has been done on the topic of understudy programs and knowledge transfer in Namibia. The objectives of this study were to investigate the implementation of the RA’s understudy programs and their management and determine the extent to which expatriates comply with the understudy policies. This study adopted a mixed research approach. Data for the study were obtained through face-to-face interviews and self-administered questionnaires. The motive behind this choice was the need to communicate only with those with experience as mentors or who have been appointed as understudies in the Roads Authority (RA). The overall findings established that the effectiveness of the understudy program was hampered by a lack of commitment, awareness and communication, and a lack of personal growth and development opportunities. In addition, the study revealed conflicting roles in work situations due to incompatible work programs, and scheduling of the program. It is recommended that RA devise formal training programs for understudies appointed to understudy expatriates and ensure that those are strictly enforced. The program should include tacit on-the-job knowledge transfer which is monitored by management on a regular basis. The program should be tailored to suit the employees’ training needs. In addition, regular information sessions should be conducted in order to sensitize all parties involved concerning the understudy policy and Affirmative Action Act, No.28 of 1998.